AN INVESTIGATION OF THE TEST SCORES IN THE CHINESE LISTENING TEST - Thu, Dinh Thi Hong (VNU Journal of Foreign Studies; Vol 36 No 2, 2020)
: In teaching-learning in general, and teaching-learning foreign languages ​​in particular, tests and exams are amongimportant forms to assess students' learning results in the learning process. A quality test can provide feedback for teaching and learning, help teachers and learners to promptly make necessary adjustments to improve the effectiveness of their teaching and learning. This research would preliminarily evaluate the quality of the test in Chinese listening for students at elementary level of proficiency based on the analysis of test papers and test scores of SC1, SC2. The research consists of 2 main parts: 1. Description and analysis of the tests; 2. Analysis of students’ test scores, and determination of the validity, reliability and difficulty of the tests using SPSS and Excel. The research results provide more feedback for subsequent test development and improvement.